Severity of grinder injuries and related factors compared with other high-rotation cutting tool injuries: a multicenter retrospective study from 2011 to 2018 - Juni Song; Yang Bin Jeon; Jae Ho Jang; Jin Seong Cho; Jae Yeon Choi; Woo Sung Choi (Journal of Trauma and Injury)
Purpose This study aimed to identify the characteristics of patients injured by high-rotation cutting tools and the factors related to the severity of their injuries. Methods Adult patients (≥18 years), who presented to the emergency department (ED) after a high-rotation cutting tool injury and who were registered in the Korean Emergency Department-based Injury In-depth Surveillance (2011–2018) database, were included. Patients’ demographic characteristics, injury-related factors, and Injury Severity Scores were collected. All included cases were categorized into two groups according to the tool that caused the injury: grinder versus nongrinder. The characteristics of the two groups were compared, and the factors associated with the severity of injuries were investigated. Results Among 8,697 ED visits, 4,603 patients had been using a grinder and 4,094 had been using a nongrinder tool. The most frequently injured body part while using a grinder was the hand (46.4%), followed by the head (23.0%). While using a nongrinder tool, the most frequently injured body part was also the hand (64.0%), followed by the lower leg (11.4%). The odds of a severe injury were affected by patient age (odds ratio [OR], 1.024; 95% confidence interval [CI], 1.020–1.028) and using a grinder (OR, 2.073; 95% CI, 1.877–2.290). The odds of a severe injury using a grinder were higher in arm injuries (OR, 1.60; 95% CI, 1.40–1.83) and multiple-part injuries (OR, 1.998; 95% CI, 1.639–2.437). The odds of a severe injury using a grinder were lower for head injuries (OR, 0.481; 95% CI, 0.297–0.781). Conclusions Injuries from grinders were more likely to affect the head and neck than nongrinder injuries, despite the lower severity. The current lack of regulations on grinders in occupational safety and health standards warrants relevant legislation and the development of applicable safety equipment.